2009
DOI: 10.1002/art.24699
|View full text |Cite
|
Sign up to set email alerts
|

A phase II, randomized, double‐blind, placebo‐controlled, dose‐ranging study of belimumab in patients with active systemic lupus erythematosus

Abstract: Objective. To assess the safety, tolerability, biologic activity, and efficacy of belimumab in combination with standard of care therapy (SOC) in patients with active systemic lupus erythematosus (SLE). Methods. Patients with a Safety of Estrogens in Lupus Erythematosus: National Assessment (SELENA) version of the Systemic Lupus Erythematosus Disease Activity Index (SLEDAI) score >4 (n ‫؍‬ 449) were randomly assigned to belimumab (1, 4, or 10 mg/kg) or placebo in a 52-week study. Coprimary end points were the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

29
432
1
13

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 521 publications
(478 citation statements)
references
References 41 publications
29
432
1
13
Order By: Relevance
“…Increases in memory B cells (CD20+/CD27+) occurred in the 10 mg/kg group. The mechanism underlying this increase in memory B cells may include release of memory B cells from disrupted lymphoid tissue, inhibition of the return of memory B cells to germinal centers, or the promotion of differentiation of naïve cells to memory B cells, although the latter may be less likely with effective binding of BLyS by belimumab11,12. The serum immunoglobulins (IgA, IgG and IgM) and autoantibodies (anti-dsDNA antibody and ANA) were not consistent and did not follow a trend in all the treatment groups.…”
Section: Discussionmentioning
confidence: 99%
“…Increases in memory B cells (CD20+/CD27+) occurred in the 10 mg/kg group. The mechanism underlying this increase in memory B cells may include release of memory B cells from disrupted lymphoid tissue, inhibition of the return of memory B cells to germinal centers, or the promotion of differentiation of naïve cells to memory B cells, although the latter may be less likely with effective binding of BLyS by belimumab11,12. The serum immunoglobulins (IgA, IgG and IgM) and autoantibodies (anti-dsDNA antibody and ANA) were not consistent and did not follow a trend in all the treatment groups.…”
Section: Discussionmentioning
confidence: 99%
“…Belimumab binds to and inhibits the activity of soluble human B lymphocyte stimulator protein 10. A placebo‐controlled phase II study showed that intravenous (IV) belimumab plus standard therapy was generally well tolerated 11; a good safety profile was maintained over 7 years 12. Two phase III studies, the Study of Belimumab in Subjects with SLE 52‐week (BLISS‐52) and 76‐week (BLISS‐76) trials, demonstrated the safety and efficacy of belimumab in patients with autoantibody‐positive, active SLE 13, 14.…”
mentioning
confidence: 99%
“…This association may be not only a clue to understanding the pathological mechanism of PCNSL but also an aid to developing treatment applications. Belimumab, a B cell stimulator inhibitor, has significantly reduced systemic lupus erythematosus disease activity 18. The agents that modulate the BAFF system molecule may thus be useful in PCNSL treatment.…”
Section: Discussionmentioning
confidence: 99%